On the Role of Input in Second Language Acquisition: The Case of French Strong Pronouns. Issue 3 (2nd July 2018) - Shimanskaya, Elena
Abstract: This study examined the acquisition of a linguistic property that is underrepresented in the input available to second language (L2) learners, namely, interpretation of French strong pronouns as [–animate]. To understand how pronouns are used and interpreted and how this topic is treated in pedagogical grammars, three types of analyses were conducted: corpus analysis, review of pedagogical materials, and experimental study with native and L2 speakers of French. Corpus data suggested that French strong pronouns were not inherently specified as [+animate] and that native speakers used these forms to refer to inanimate objects, at least when strong pronouns were used as objects of prepositions. Additionally, experimental data revealed that advanced L2 speakers also accepted inanimate interpretations. Taken together, the findings suggested that targetlike interpretation of pronouns can be acquired despite the scarcity of input, negative transfer from learners' first language, and lack of explicit instruction of the target property.